TINGKAT REDUKSI EROSI DAN ALIRAN PERMUKAAN TERHADAP TANAMAN KAKAO (Theobroma Cocoa L) DEWASA DI DAS NOPU - Ramlan Ramlan (Universitas Tadulako, 2009)
The aims of the research were to study the rate of top soil erosion, to determine actual erosion and C factor under different land uses in the Nopu watershed. Field experiment was conducted from January to March 2006 in the upper Nopu watershed, Palolo sub district, Donggala regency. Soil physical analyses were done in Soil Science Laboratory of Agricultural Faculty of Tadulako University. Small plots were purposively determined for erosion experiment. The result of the research showed that soil physical characteristics such as bulk density, porosity, aggregate stability index, texture, and soil organic matter under cacao land use were different from those under bare land use. The actual soil erosion under bare land use with 10% slope was much higher than that under cacao land use which were 14,304.49 and 172.6 kg/ha/yr, respectively.